PENGARUH MASA PERIKATAN AUDIT, SPESIALISASI INDUSTRI KAP, REPUTASI KAP DAN KOMITE AUDIT TERHADAP KUALITAS AUDIT (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR DI BEI TAHUN 2011-2014) - Pertiwi, Nastia Putri; Hasan, Amir (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2016)
This study aimed to determine effect of period audit engagements, industryspecialization accounting firm, accounting firms reputation and the audit committeeon audit quality. This study uses three control variables, namely leverage, LOSS andcash flow from operations. The data used in this research is secondary data derivedfrom the financial statements of companies listed on the Indonesia Stock Exchangein 2011-2014. By using purposive sampling, this study got 92 sample companies.The data analysis method used in this research is multiple linear regression. Theresults showed period audit engagements and industry specialization accountingfirm has no effect on audit quality, while the reputation of accounting firm and theaudit committee kualtitas affect the audit. Of the three control variables used in thisstudy, only a leverage effect on audit quality, while LOSS and cash flow fromoperation has no effect.Keywords: Period of the audit engagement, industrial specialties accounting firm,accounting firms reputation, the audit committee and audit quality.